In: "Adolf Hitler. Bilder aus dem Leben des Führers" (1936). Hitler weiht die Standarten von der SA (1935)
In: "Adolf Hitler. Bilder aus dem Leben des Führers" (1936). Hitler weiht die Standarten von der SA.